Hubungan Pungutan Liar terhadap Kesejahteraan Masyarakat di Bekasi - Dini Iswari Amaliani; Fandhi Abiyyu Akmal; Laila Azizah; Nursyaniah Siregar; Putri Satya Permana; Mic Finanto Ario Bangun (Concept: Journal of Social Humanities and Education, 2025)
The main goal in improving the governance of correctional institutions is to realise a clean correctional, but there are obstacles in the process of achieving it. One of them is about the problem of illegal levies that are still raging and rampant in the Penitentiary environment, Pungli (wild levies) not only harms inmates and their families, but becomes one of the inhibiting factors in achieving a clean transformation of corrections.The purpose of this research is to describe and explain the causes and efforts to eradicate illegal levies in the Penitentiary environment in order to realise a prosperous community life. The research method used is research by reviewing literature studies. The data collection technique in this research is carried out by searching and analysing various literature sources such as journals and scientific articles searched through the official website in the form of Google Scholar.The results of the research show that the cause of illegal levy behaviour in the community is due to the inefficiency of providing services to the community and is too complicated, this can be one of the causes of opening a gap for individuals to practice illegal levies. As for the countermeasures that have been carried out by the security parties who are responsible in terms of inj, among others, are carrying out routine patrols.